Co-encapsulation of a Drug with a Protein in Erythrocytes for Improved Drug Loading and Release: Phenytoin and Bovine Serum Albumin (BSA) - Mehrdad Hamidi; Kourosh Azimi; Soliman Mohammadi-Samani (Frontiers Media S.A., 2011)
The aim of the present study was to use a novel protein co-encapsulation method to prepare phenytoin-loaded human erythrocytes with improved loading parameters and release profiles. Carrier erythrocytes were prepared using the hypotonic pre-swelling method. A series of in vitro characterization tests were carried out on the carrier cells, including loading parameters, drug and hemoglobin release, hematological indices, particle size analysis, osmotic fragility, turbulence fragility, and scanning electron microscopy (SEM). Co-encapsulation with bovine serum albumin (BSA) resulted in about 8-times higher drug loading in erythrocytes, with biphasic release trend instead of triphasic in the case of drug alone loading. In comparison to the normal unloaded cells, MCH and MCHC indices were decreased in the case of both drug and drug/protein loading, apparent cell sizes were unchanged, cell shapes were changed to spherical rather than biconcave discoid, and the osmotic as well as turbulence fragilities were higher in the case of drug/protein but were unchanged in the case of drug alone loading. The most profound finding of this study was the possibility of achieving remarkably higher drug loading and more controllable drug release profile in the case of drug/protein loading, with no unwanted in vitro characteristics change.